Management of Atrial Fibrillation Using Immunoglobulin Free Light Chains, Novel Biomarkers of Inflammation - Akira Matsumori (European Cardiology Review)
AF is the most common cardiac arrhythmia. There is growing evidence that inflammatory mechanisms play an important role in its pathogenesis; inflammasome activation contributes to the onset and progression of AF. An increase in NOD-like-receptor-pyrin domain-containing-3 (NLRP3) inflammasome activation releases proinflammatory cytokines that activate nuclear factor (NF)-κB, which regulates the production of immunoglobulin free light chains (FLCs). Serum FLC levels are increased in patients with AF, and FLCs are biomarkers of inflammation. Inflammasomes and NF-κB may be targets for anti-inflammatory strategies to prevent and treat AF when FLC levels are elevated. This review discusses the role of inflammation in the pathogenesis of AF, as well as FLCs as novel inflammatory biomarkers for the management of AF.